Application of Project-Based Learning Model with Pixton in the Development of Teaching Module Grade VII Fantasy Text Material - Moch. Irsyadul Ibad; Elva Riezky Maharany (Yayasan Keluarga Guru Mandiri, 2025)
The development of teaching modules based on digital media for fantasy text materials can help improve students' cognitive abilities. Based on the initial interview conducted on September 17, 2024, it was found that only around 45.9% of students achieved scores above the passing grade in Indonesian lessons, with an average through the application of the PjBL model. It is hoped that it can improve the quality of interaction between educators and students, as well as help students at MTs Almaarif 01 Singosari understand and foster critical thinking, creativity, and collaboration with Indonesian materials, especially in fantasy story texts. The approach used is the Research and Development approach, involving two classes: the development class and the control class, and ADDIE's research model for data collection. The findings of this study indicate that the use of Pixton as a teaching medium is effective in improving students' learning comprehension results, with an average score increase of 20.3, and consistently enhancing the quality of learning. The development of this research is expected to increase the contribution and readiness of educators to face various technological challenges in education in the future.